2014
DOI: 10.4141/cjps2013-118
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a quality testing program for improving malting barley in Canada

Abstract: 2014. Evolution of a quality testing program for improving malting barley in Canada. Can. J. Plant Sci. 94: 535Á544. The quality of Canadian malting barley has continually improved since malt barley was exported in the late 1800s. Improvements were linked to a dynamic evaluation system that evolved with a better understanding of malting biochemistry and as suitable methods were developed. Methods became more accurate and more specific in their ability to define quality. They progressed from sensory evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Brewing technology itself contributes also to the final β-glucan content in wort. Edney et al (2012Edney et al ( , 2014 reported wort β-glucan content ranging from 60 to 140 mg/L for Canadian barley varieties. Even though there are no recommendations for brewers regarding total β-glucan content in malt, for wort it is recommended it should not exceed 200 mg/L (Davis 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Brewing technology itself contributes also to the final β-glucan content in wort. Edney et al (2012Edney et al ( , 2014 reported wort β-glucan content ranging from 60 to 140 mg/L for Canadian barley varieties. Even though there are no recommendations for brewers regarding total β-glucan content in malt, for wort it is recommended it should not exceed 200 mg/L (Davis 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the measurement and development of new technologies/methods that measure new aspects of quality not considered or understood in the past will allow a better understanding of malt quality to better facilitate product development and improve efficiencies in the brewing process as well as to develop or improve barley varieties (Edney et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] However, the current state of knowledge of their exact biochemical, chemical and physiological roles and their effects on the biophysical properties of grains is still incomplete. [20][21][22][23][24] Biochemical components of grain other than starch such as proteins, non-structural, structural polysaccharides and lipids inuence or modulate the quality of the grain and consequently its malting properties. [13][14][15][16][17][18] In most cereals, most of the sucrose might be converted into starch, where the conversion into lipids accounts for less than 5% of the total carbon pool in the plant.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Sucrose serves as one of the main carbon sources for the synthesis of membrane lipids, phospholipids, non-storage proteins and enzymes. 20,24 New technologies or methods that measure new aspects of malt quality not considered or understood in the past will allow a better understanding of the main drivers of composition, to better facilitate product development and to improve efficiencies in the brewing process as well as to develop or improve barley varieties. 16 In foods, the presence of sugar fatty esters (e.g., sucrose esters, glycolipids) can also determine several rheological properties and in particular they have been used as emulsiers in ice cream and bread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation